Changing Cities - Changing Minds. - Ryser, Judith (My University, 2015)
Long established planning practices are hard to overcome. Top down control mechanisms remain in place with little devolution and self-determination. In many countries ministers can overrule elected regions and municipalities and governments continue to hold the purse strings, invoking national interest to legitimise their reserve powers. Although conventional wisdom claims that cities are the drivers of future prosperity, many city dwellers undergo precarious employment, expensive commuting, overpriced housing, congestion, pollution and erosion of the public realm, undermining their quality of life. Disillusioned by party politics, some are turning to alternatives. Out of necessity, a parallel universe is emerging in urban areas, also in the developed world, relying on own resources and contributing creatively to a 'vibrant city'. Yet, activists may become the victims of their own success when the developing industry reaps the benefits of their efforts, not seldom acquiesced by planning. The motivation of this paper is not just a 'vibrant city' but a more equitable and inclusive city. It draws on twelve cities in north-west Europe where dynamic stakeholders are realising their aspirations by reinventing planning in cooperation with bottom-up forces.
Keywords: Stadtplanung; Stadtentwicklung; Planungspraxis; Planungsprozess; Partizipation; Beteiligung